Sustainability Status of Seaweed Kappaphycus alvarezii Cultivation in Posi-Posi Waters, South Kayoa Subdistrict, Regency of South Halmahera, Province of North Mollucas, Indonesia - Muhammad Irfan, Nursanti Abdullah, Yuliana, Gamal M. Samadan; Riyadi Subur (International Journal of Advanced Science and Technology, 2020)
Seaweed cultivation is much in demand by the people in the Posi-Posi villages because of the large business potential and in accordance with their area. Seaweed has high value and benefit value so that it can improve the standard of living of the people who live in the area. The purpose of this study was to see the status of seaweed K. alvarezi cultivation sustainable in Posi-Posi waters South Kayoa Sub-district, Regency of South Halmahera, Province of North Mollucas. This research lasted for six months from May 2018 to October 2018 in Posi-Posi waters Regency of South Halmahera, Province of North Mollucas. Data collection using survey methods through observation and interviews. The results obtained that the status of seaweed K.alvarezi sustainable cultivation is seen from five dimensions (ecology, economics/financial, technical ,socio-cultural and institutional), showing that two good sustainable dimensions are ecological and technical dimensions, then two less sustainable dimensions namely economic/financial and institutional dimensions, and one unsustainable dimension, the socio-cultural dimension, while multidimensionally obtained the status is quite sustainable.